Job insecurity, extrinsic and intrinsic job satisfaction and affective organisational commitment of maintenance workers in a parastatal - J. H. Buitendach; H. De Witte (South African Journal of Business Management, 2005)
The objective of this study was to assess the relationship between job insecurity, job satisfaction and affective organisational commitment of maintenance workers (N = 178) in a parastatal in Gauteng. A cross-sectional design was used. Stratified random samples of maintenance workers (N = 178) were taken. The Job Insecurity Inventory, Minnesota Job Satisfaction Questionnaire and Organisational Commitment Questionnaire were used as measuring instruments. The results revealed small but significant relationships between job insecurity and extrinsic job satisfaction and job insecurity and affective organisational commitment. Job satisfaction was found to mediate the relationship between job insecurity and affective organisational commitment.
Keywords: 650